Desarrollo e implementación de un plan integral de continuidad del negocio en una empresa que presta servicio de mantenimiento y reparación de equipos de audio y video, línea blanca y computadoras para el año 2009. - Fiallos, O. (2009)
This work presents the development and implementation of an integral Business Continuity Plan for year 2009 in a company that provides maintenance and repair service of audio and video equipment, home appliances and computers. For this development, we include a brief description of the company, an analysis and evaluation of the potential risks and threats to which the company is exposed to. We have developed Business Impact Analysis (BIA), which analyzes the financial and operation impact of events that may disrupt any areas and procedures of the business. Also, continuity strategies have been developed; an Emergency committee team has been presented whose main objective is the creation of a written plan detailing the actions, procedures and resources that must be used during the disruption event. Moreover, various recovery alternatives will be developed in case of any emergency affects the business. A series of test will determine, within an acceptable timeframe, if the BCP is adequate for the recuperation of the company. We also include the plan’s maintenance phase and finally we present the conclusion and recommendation of the work done.